2022
DOI: 10.3390/pharmacy10060172
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Evening Primrose (Oenothera biennis) Preparations for the Facilitation of Parturition

Abstract: Background: The objective of this systematic review was to characterize the efficacy and safety of evening primrose (EP) for facilitation of parturition in peripartum persons. Methods: This search sought records related to the efficacy and safety of EP preparations to facilitate parturition. Eligibility criteria were primary literature with efficacy or safety outcomes reported; studied in peripartum persons; and available in English. Records were excluded if they were available as abstracts only. Data was synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…For short-term use, the normal oral dose is 6 g per day; however, there is no recommended topical or vaginal dose in previous guidelines. 33 From 2.7 to 4.4 h, GLA was found to reach the highest plasma level. However, the topically or vaginally administered EPO has not been investigated yet regarding its absorption rate, distribution in tissues, metabolism, and excretion.…”
Section: Digestion Absorption and Possible Effect On Gut Microbiotamentioning
confidence: 90%
See 4 more Smart Citations
“…For short-term use, the normal oral dose is 6 g per day; however, there is no recommended topical or vaginal dose in previous guidelines. 33 From 2.7 to 4.4 h, GLA was found to reach the highest plasma level. However, the topically or vaginally administered EPO has not been investigated yet regarding its absorption rate, distribution in tissues, metabolism, and excretion.…”
Section: Digestion Absorption and Possible Effect On Gut Microbiotamentioning
confidence: 90%
“…However, the topically or vaginally administered EPO has not been investigated yet regarding its absorption rate, distribution in tissues, metabolism, and excretion. 33 Another clinical study in 6 healthy volunteers receiving six capsules of Epogam® (total dose being 240 mg of GLA) twice daily showed that absorption from the digestive tract is significantly lower in the morning compared to the evening. 34 Liquid EPO has been reported to deliver pure oil in a readily absorbable form.…”
Section: Digestion Absorption and Possible Effect On Gut Microbiotamentioning
confidence: 99%
See 3 more Smart Citations